Effects of Mead Wort Heat Treatment on the Mead Fermentation Process and Antioxidant Activity - Sławomir Czabaj; Joanna Kawa-Rygielska; Alicja Z. Kucharska; Jarosław Kliks (Molecules, 2017)
The effects of mead wort heat treatment on the mead fermentation process and antioxidant activity were tested. The experiment was conducted with the use of two different honeys (multiflorous and honeydew) collected from the Lower Silesia region (Poland). Heat treatment was performed with the use of a traditional technique (gently boiling), the more commonly used pasteurization, and without heat treatment (control). During the experiment fermentation dynamics were monitored using high performance liquid chromatography with refractive index detection (HPLC-RID). Total antioxidant capacity (TAC) and total phenolic content (TPC) were estimated for worts and meads using UV/Vis spectrophotometric analysis. The formation of 5-hydroxymethylfurfural (HMF) was monitored by HPLC analyses. Heat treatment had a great impact on the final antioxidant capacity of meads.